Formulation Study of a Co-Processed, Rice Starch-Based, All-in-One Excipient for Direct Compression Using the SeDeM-ODT Expert System - Karnkamol Trisopon; Nisit Kittipongpatana; Phanphen Wattanaarsakit; Ornanong Suwannapakul Kittipongpatana (MDPI AG, 2021)
A co-processed, rice starch-based excipient (CS), previously developed and shown to exhibit good pharmaceutical properties, is investigated as an all-in-one excipient for direct compression (DC). An SeDeM-ODT expert system is applied to evaluate the formulation containing CS, in comparison with those containing the physical mixture and the commercial DC excipients. The results revealed that CS showed acceptable values in all six incidence factors of the SeDeM-ODT diagram. In addition, the comprehensive indices (IGC and IGCB) were higher than 5.0, which indicated that CS could be compressed with DC technique without additional blending with a disintegrant in tablet formulation. The formulation study suggested that CS can be diluted up to 60% in the formulation to compensate for unsatisfactory properties of paracetamol. At this percentage, CS-containing tablets exhibited narrow weight variation (1.5%), low friability (0.43%), acceptable drug content (98%), and rapid disintegration (10 s). The dissolution profile of CS displayed that more than 80% of the drug content was released within 2 min. The functionality of CS was comparable to that of high functionality excipient composite (HFEC), whereas other excipients were unsuccessful in formulating the tablets. These results indicated that CS was a suitable all-in-one excipient for application in DC of tablets.